2010
DOI: 10.1007/s00421-009-1342-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing and fitness on skin-microvessel vasodilator function in humans

Abstract: The impact of cardiopulmonary fitness (VO(2max)) on the age-related decline in skin-microvessel vasodilator function has not been fully established and the inter-relationships among different measures of microvascular vasodilator function are unknown. We used laser Doppler flowmetry to assess relative changes in forearm skin blood flow to various stimuli in three groups of adults: young (n = 15; 27 +/- 2 years), older sedentary (n = 14; 65 +/- 6 years) and older fit (n = 15; 61 +/- 5 years). Local-heating indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 44 publications
9
61
1
Order By: Relevance
“…This suggests that only minor damage occurred due to intrinsic aging compared to photoaging. It was reported that senescence is associated with an attenuated vasodilation response and reduced melanocyte numbers [31,32]. Our results confirmed these phenomena by macroscopic observation and erythema detection.…”
Section: Discussionsupporting
confidence: 95%
“…This suggests that only minor damage occurred due to intrinsic aging compared to photoaging. It was reported that senescence is associated with an attenuated vasodilation response and reduced melanocyte numbers [31,32]. Our results confirmed these phenomena by macroscopic observation and erythema detection.…”
Section: Discussionsupporting
confidence: 95%
“…No specific interaction was found between nerve blockade and age. Unlike the forearm, the NO-dependent plateau phase is minimal, and is not significantly diminished on the supramedial malleolar skin of the elderly volunteers (Minson et al, 2002;Tew et al, 2010). Unlike on the forearm, in supramedial malleolar skin the late LTH plateau remained stable without dwindling away, until beyond 60 min in both the younger and older groups.…”
Section: Discussionmentioning
confidence: 52%
“…In recent years, a few teams showed that both the axon reflex and NO-dependent cutaneous vasodilation during local heating on the forearm is altered with age (Minson et al, 2002;Tew et al, 2010). Again on the forearm, abnormal initial peak and late plateau in response to local heating were further confirmed in non-neuropathic and neuropathic older subjects (Fromy et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations